Deciphering the Role Played by Autophagy in Leishmania Infection - Veras, Patricia Sampaio Tavares; de Menezes, Juliana Perrone Bezerra; Dias, Beatriz Rocha Simões (Frontiers in Immunology, 2019)
In recent decades, studies have shown that, depending on parasite species and host background, autophagy can either favor infection or promote parasite clearance. To date, relatively few studies have attempted to assess the role played by autophagy in Leishmania infection. While it has been consistently shown that Leishmania spp. induce autophagy in a variety of cell types, published results regarding the effects of autophagic modulation on Leishmania survival are contradictory. The present review, after a short overview of the general aspects of autophagy, aims to summarize the current body of knowledge surrounding how Leishmania spp. adaptively interact with macrophages, the host cells mainly involved in controlling leishmaniasis. We then explore the scarce studies that have investigated interactions between these parasite species and the autophagic pathway, and finally present a critical perspective on how autophagy influences infection outcome.